Correlation between Academic Evaluation Scores within the Undergraduate Medical Education: A Cross-sectional Study - Atik, Nur; Talitha, Devina; Dwiwina, Resti Gradia; Berbudi, Afiat; Sari, Nur Melani; Dewi, Putu Indra Cyntia; Rahmani, Nada Ristya (Indian Journal of Pharmaceutical Education and Research, 2020)
Introduction: There are several evaluations to assess the medical students finishing the courses. Examinations could be multiple-choice questions that tend to evaluate the memorization rather than analytical ability. Another is oral examination tests that evaluate the ability in analysing the specific cases. However, though the oral examination assesses by two examiners, still the subjectivity of the examiner cannot be ignored. This study aims to provide insight on the correlation between test scores of multiple choice question and oral examination in the medical undergraduate program. Methods: The cross sectional study included test scores from first to fourth year medical undergraduate students at Faculty of Medicine, Padjadjaran University. Scores were collected from the Multiple Disciplinary Examination (MDE), a summative multiple choice exam; and Student’s Objective Oral Case Analysis (SOOCA), a summative case analysis oral exam. Test scores analysed were initial scores prior to remedial. Spearman’s correlation test was used to analyse correlation between scores. Results: A total of 1031 corresponding sets of MDE and SOOCA test scores were collected. Spearman test showed a positive and significant correlation between MDE and SOOCA scores of all study courses throughout the year. The strongest correlation was found in the sixth semester within the Gastrointestinal System and Genitourinary System Block (rs=0.571 (p< 0.01). The weakest correlation was found in the first semester within the Fundamental Basic Science II Block (rs=0.197 (p< 0.01)). Conclusion: There is a positive correlation between test scores from multiple-choice question examinations and oral examination scores. Both tests complement each other in evaluating medical undergraduate education.
Keywords: Education; Evaluation studies; Medical students; Undergraduates